Magnetic field-temperature phase diagram, exchange constants and specific heat exponents of the antiferromagnet MnNb2O6. (1st July 2021) - R, Maruthi; Ghosh, Sayandeep; Seehra, Mohindar S; Joshi, Deep C; Chowdhury, Mouli R; Medwal, Rohit; Rawat, Rajdeep S; Weise, Bruno; Thota, Subhash
Abstract: This work presents the magnetic field-temperature ( H – T ) phase diagram, exchange constants, specific heat ( C P ) exponents and magnetic ground state of the antiferromagnetic MnNb2 O6 polycrystals. Temperature dependence of the magnetic susceptibility χ (= M / H ) yields the Néel temperature T N = 4.33 K determined from the peak in the computed ∂( χT )/∂ T vs T plot in agreement with the transition in the C P vs T data at T N = 4.36 K. The experimental data of C P vs T near T N is fitted to C P = A | T − T N | − α yielding the critical exponent α = 0.12 (0.15) for T > T N ( T < T N ). The best fit of χ vs T data for T > 50 K to χ = χ 0 + C /( T − θ ) with χ 0 = −1.85 × 10 −4 emu mol −1 Oe −1 yields θ = −17 K, and C = 4.385 emu K mol −1 Oe −1, the latter giving magnetic moment μ = 5.920 μ B per Mn 2+ ion. This confirms the effective spin S = 5/2 and g = 2.001 for Mn 2+ and the dominant exchange interaction being antiferromagnetic in nature. Using the magnitudes of θ and T N and molecular field theory (MFT), the exchange constants J 0 / k B = −1.08 K for Mn 2+ ions along the chain c -axis and J ⊥ / k B = −0.61 K as the interchain coupling perpendicular to c -axis are determined. These exchange constants are consistent with the expected χ vs T variation for the Heisenberg linear chain. The H – T phase diagram, mapped using the M – H isotherms and M – T data at different H combined with the reported data of Nielsen et al, yields a triple-point T TP ( H, T ) = (18 kOe, 4.06 K). The spin–flopped state above T TP and the forced ferromagnetism for H > 192 kOe are used to estimate the anisotropy energy H A ≈ 0.8 kOe.